2021
DOI: 10.1002/jbm.b.34857
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and in vitro biological properties of uniform and graded Cobalt‐chrome lattice structures in orthopedic implants

Abstract: Human bones are biological examples of functionally graded lattice capable to withstand large in vivo loading and allowing optimal stress distribution. Disruption of bone integrity may require biocompatible implants capable to restore the original bone structure and properties. This study aimed at comparing mechanical properties and biological behavior in vitro of uniform (POR-FIX) and graded (POR-VAR) Cobaltchrome alloy lattice structures manufactured via Selective Laser Melting. In compression, the POR-VAR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…The material of cobalt alloys is tough, and the surface chromium oxide layer provides corrosion resistance. Nevertheless, because of its hardness, creating complex shapes and its machining are challenging [21,22]. Commercial titanium is highly biocompatible and corrosion resistant; however, it lacks sufficient mechanical strength.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material of cobalt alloys is tough, and the surface chromium oxide layer provides corrosion resistance. Nevertheless, because of its hardness, creating complex shapes and its machining are challenging [21,22]. Commercial titanium is highly biocompatible and corrosion resistant; however, it lacks sufficient mechanical strength.…”
Section: Metalsmentioning
confidence: 99%
“…Various in vitro studies have shown the potential application of 3D-printed scaffolds in BTE [6,22,27,33]. CaP ceramics and bioactive glasses are introduced as promising osteoinductive and osteoconductive substitutes for large orthopedic defect remolding or regeneration [4,6,69,70].…”
Section: Customized Scaffoldsmentioning
confidence: 99%
“…Cobalt-based alloys Some Co-Cr based alloys are the most preferred metallic biomaterials in orthopedic applications, especially in hip prostheses and dental applications (e.g. CoCrMo, CoCr, CoCrCu and CoCrW), for that reason, all the improvements on its mechanical performance are justified (AlMangour et al, 2020;Dobrza nski et al, 2020;Lu, 2017;Pagani et al, 2021;Uzun, 2019). A personalized femoral component of CoCrMo (CCM) with good exterior quality, mechanical property and biological corrosion resistance, obtained by the SLM process, was the achievement of the work proposed by Song (2016).…”
Section: Aluminum-based Alloysmentioning
confidence: 99%
“…No attempt was made to explore the effects of varying process parameters beyond those described in a previous work [15], summarized in Table 1. A 3 × 3 mm chessboard scanning strategy was used for hatching.…”
Section: Design and Manufacturingmentioning
confidence: 99%
“…Lattice structures have also been successfully applied to the fabrication of biomedical devices to enhance osseointegration and/or to reduce stress shielding phenomena [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%